Однажды в одном королевстве: [сказки] / О. Аверин - Аверин Олег Георгиевич (Серия "Малышкины книжки", 2011)
Экземпляры: ф. 3 (20120613) / Инвентарный номер: 98723 / Цена: 60.00 / Авт.знак: А 19 / ББК: 84(2Рос=Рус)6